Hydrophilic ceftriaxone magnetic molecularly imprinted polymer as well as preparation method and application thereof
The hydrophilic ceftriaxone magnetic molecular imprinted polymers are prepared by using magnetic iron-aluminum mixed hydroxide and ceftriaxone in aqueous solution, which solves the problem that cannot be measured in the water environment in the prior art, and achieves efficient and green adsorption and determination of cephalosporin antibiotics.
Patent Information
- Application Number
- CN202411708239.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-27
- Publication Date
- 2025-02-25
- Estimated Expiration
- 2044-11-27
AI Technical Summary
The existing ceftriaxone magnetic molecular imprinted polymers are synthesized in non-polar organic solvents and cannot be used for the determination of cephalosporin antibiotics in aqueous environments. The preparation process requires a large number of organic or toxic solvents, which consumes time and energy consumption.
Magnetic iron-aluminum mixed hydroxide is used as the carrier, ceftriaxone is used as the template molecule, 3-amino-1,2,4-triazole is the functional monomer, ethylene glycol dimethacrylate is the crosslinking agent, ammonium persulfate is the initiator, and water is the pore-generating agent, to prepare hydrophilic ceftriaxone magnetic molecular imprint polymer.
The hydrophilic ceftriaxone magnetic molecular imprinted polymer prepared has high magnetization and stable morphological structure, has good adsorption properties for ceftriaxone, and can effectively identify and adsorb cephalosporin antibiotics in a water environment, simplifying the operation steps and reducing energy consumption.
Smart Images

Figure CN119505344A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a hydrophilic ceftriaxone magnetic molecular imprinted polymer and a preparation method and application thereof, belonging to the technical field of magnetic molecular imprinted polymer preparation. Background Art
[0002] Ceftriaxone (CEF) is a β-lactam antibiotic with a broad antibacterial spectrum and stability against β-lactamase. It is widely used in livestock and poultry farming and aquaculture. However, if used in violation of regulations, the drug residue will not only affect the development of the breeding industry, but also pose a serious threat to the environment and human health.
[0003] Solid Phase Extraction (SPE) is the most commonly used pretreatment technology for the detection of antibiotic residues in complex samples (biological, food, environment, etc.). Among them, magnetic dispersed solid phase extraction (MDSPE) uses magnetic materials as carriers and has the advantage of rapid separation. It is a widely used drug residue pretreatment technology. Molecularly imprinted polymers (MIPs) have advantages in improving target selectivity, recognition and detection sensitivity. Magnetic molecularly imprinted polymers (MMIPs) synthesize molecular imprinting shells on the surface of magnetic nanoparticles. They not only have the advantages of molecular imprinting and can specifically identify and adsorb target molecules, but also simplify traditional column loading, centrifugation and filtration operations. Solid-liquid separation can be achieved through the action of an external magnetic field. In recent years, some scholars have synthesized magnetic nanoparticles of different types of MDSPE, such as Fe 3 O 4 , and GO-MWCNTs-Fe 3 O 4 In addition to the above materials, magnetic mixed metal hydroxides (MMH) have the characteristics of simple and rapid preparation, good stability, superparamagnetism, etc., and are currently a kind of magnetic material with a high utilization rate.
[0004] In order to avoid the destruction of hydrogen bonds by polar solvent water during the prepolymerization process, common MMIPs are synthesized in non-polar organic solvents and only show optimal performance in non-aqueous environments. They are not suitable for the analysis of hazards in aqueous media and have a narrow scope of application. In addition, traditional MMIPs require a large amount of organic or toxic solvents, which takes a lot of time and energy. The preparation of existing cephalosporin antibiotic magnetic molecular imprinting polymers is completed in non-polar organic solvents and is not suitable for the determination of cephalosporin antibiotics in aqueous environments. Therefore, it is of great significance to explore a green preparation method for self-assembly and regulation of hydrophilic magnetic molecular imprinting polymers that can achieve specific recognition of ceftriaxone. Summary of the invention
[0005] The invention provides a hydrophilic ceftriaxone magnetic molecular imprinted polymer and a preparation method and application thereof, which can effectively solve the above problems.
[0006] The present invention is achieved in that:
[0007] A method for preparing a hydrophilic ceftriaxone magnetic molecular imprinted polymer comprises the following steps: using magnetic iron-aluminum mixed hydroxide as a carrier, ceftriaxone as a template molecule, 3-amino-1,2,4-triazole as a functional monomer, ethylene glycol dimethacrylate as a crosslinking agent, ammonium persulfate as an initiator, and water as a porogen to prepare the hydrophilic ceftriaxone magnetic molecular imprinted polymer.
[0008] In some embodiments, the preparation method of the magnetic iron-aluminum mixed hydroxide is a co-precipitation method.
[0009] In some embodiments, (NH 4 ) 2 Fe(SO 4 )2·6H 2 O and AlCl 3 6H 2 O is added into deionized water, stirred until completely dissolved, NaOH is added, stirred for reaction, allowed to stand for stratification, the supernatant is discarded, and the black product is collected, which is the magnetic iron-aluminum mixed hydroxide.
[0010] In some embodiments, the (NH 4 ) 2 Fe(SO4) 2 6H 2 O and AlCl 3 6H 2 The molar ratio of O is 1.8-2.2:1.
[0011] In some embodiments, the specific steps of the preparation method include:
[0012] S1, preparing a magnetic iron-aluminum mixed hydroxide suspension;
[0013] S2, dissolving ceftriaxone and 3-amino-1,2,4-triazole in deionized water, and then mixing and stirring with the magnetic iron-aluminum mixed hydroxide suspension;
[0014] S3, adding ethylene glycol dimethacrylate and ammonium persulfate to the solution obtained in step S2, stirring, subjecting the mixed product to a polymerization reaction in an inert atmosphere, removing the supernatant, and collecting the product, which is the hydrophilic ceftriaxone magnetic molecular imprinting polymer.
[0015] In some embodiments, the ratio of the magnetic iron-aluminum mixed hydroxide, ceftriaxone, 3-amino-1,2,4-triazole, ethylene glycol dimethacrylate and ammonium persulfate is 8-12 g: 0.18-0.22 mmol: 3.5-4.5 mmol: 15-25 mmol: 1 g.
[0016] In some embodiments, the polymerization reaction temperature is 38-42° C., the rotation speed is 280-330 r / min, and the reaction time is 4.5-5.5 h.
[0017] In some embodiments, the hydrophilic ceftriaxone magnetic molecular imprinted polymer is dried and then washed with a methanol-acetic acid-water mixture and a sodium dihydrogen phosphate solution in sequence until no template molecules are detected in the washing solution, and then dried for later use.
[0018] A hydrophilic ceftriaxone magnetic molecular imprinted polymer prepared by the above method.
[0019] An application of the hydrophilic ceftriaxone magnetic molecular imprinted polymer in the detection of ceftriaxone.
[0020] The beneficial effects of the present invention are:
[0021] The hydrophilic ceftriaxone magnetic molecular imprinted polymer of the present invention has higher magnetization intensity and more stable morphological structure, has good adsorption performance for ceftriaxone, reaches adsorption equilibrium within 30 seconds, and the equilibrium adsorption capacity is 6.30 mg / g, which conforms to the pseudo-second-order kinetic adsorption model.
[0022] The hydrophilic ceftriaxone magnetic molecular imprinted polymer of the present invention can be directly applied to the determination of cephalosporin antibiotics in water environment, and provides technical support for the subsequent development of highly selective ceftriaxone hydrophilic magnetic dispersion solid phase extraction adsorbent. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments will be briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without paying creative work.
[0024] Figure 1 XRD patterns of (A) MMH, (B) MNIP and (C) CEF-MMIP of Examples and Comparative Examples.
[0025] Figure 2 FTIR graphs of MMH, MNIP and CEF-MMIP of Examples and Comparative Examples.
[0026] Figure 3 The transmission electron microscopy spectra of MMH (a), MNIP (b), and CEF-MMIP (c) of the embodiment and comparative example.
[0027] Figure 4 The scanning electron microscope spectra of MMH (a), MNIP (b), and CEF-MMIP (c) of the embodiment and comparative example.
[0028] Figure 5 Magnetic hysteresis loops of MMH, MNIP and CEF-MMIP of the embodiments and comparative examples.
[0029] Figure 6 The adsorption isotherms of CEF-MMIP and MNIP of Examples and Comparative Examples are shown in FIG.
[0030] Figure 7 Scatchard curves of CEF-MMIP and MNIP of Examples and Comparative Examples.
[0031] Figure 8 The Langmuir model diagrams of the embodiments and comparative examples are shown in FIG.
[0032] Fig. 9 The Freundlich model diagrams of the embodiments and comparative examples are shown in FIG.
[0033] Fig.10 The kinetic adsorption curves of CEF-MMIP and MNIP of the examples and comparative examples are shown in FIG.
[0034] Fig.11 It is the first-order kinetic fitting diagram of embodiment and comparative example.
[0035] Fig.12 It is the second-order kinetic fitting diagram of the embodiment and comparative example. DETAILED DESCRIPTION
[0036] In order to make the purpose, technical solutions and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention. Therefore, the following detailed description of the embodiments of the present invention provided in the drawings is not intended to limit the scope of the invention claimed for protection, but merely represents the selected embodiments of the present invention. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0037] The embodiment of the present invention relates to a method for preparing a hydrophilic ceftriaxone magnetic molecular imprinted polymer. The method comprises the following steps: first, a magnetic iron-aluminum mixed hydroxide is selected as a carrier material, which has good magnetic responsiveness and stability. Next, ceftriaxone is used as a template molecule, which has a specific chemical structure and biological activity and can guide the formation of a polymer. Then, 3-amino-1,2,4-triazole is selected as a functional monomer, which can specifically bind to the ceftriaxone molecule through hydrogen bonds or other interaction forces. In addition, ethylene glycol dimethacrylate is used as a cross-linking agent to ensure the stability and rigidity of the polymer network structure. Ammonium persulfate is used as an initiator to initiate a free radical polymerization reaction in an aqueous solution to form a polymer network. Finally, water is used as a porogen to form a pore structure during the polymerization process, thereby increasing the specific surface area and adsorption performance of the polymer. Through the above steps, a ceftriaxone magnetic molecular imprinted polymer with excellent hydrophilicity and specific recognition ability can be successfully prepared.
[0038] In some specific embodiments, the method for preparing magnetic iron-aluminum mixed hydroxide can be a coprecipitation method. Specifically, in these embodiments, a certain amount of (NH 4 ) 2 Fe(SO 4 ) 2 6H 2 O (ammonium ferric sulfate) and AlCl 3 6H 2O (aluminum chloride hexahydrate) is dissolved in deionized water. By stirring thoroughly, ensure that these salts are completely dissolved in the water. Subsequently, an appropriate amount of NaOH (sodium hydroxide) is added to the solution and stirring is continued to promote the reaction. After the reaction is completed, the mixture is allowed to stand and the layers are separated so that the precipitate can be separated. Finally, the supernatant is discarded, and the remaining black precipitate is the desired magnetic iron-aluminum mixed hydroxide. In this way, iron-aluminum mixed hydroxides with specific magnetic properties and chemical compositions can be effectively prepared, which are suitable for a variety of industrial and scientific research applications.
[0039] In some embodiments, the (NH 4 ) 2 Fe(SO 4 ) 2 6H 2 O and AlCl 3 6H 2 The molar ratio of O is 1.8-2.2:1. This molar ratio range can ensure the effective combination between the reactants, thereby achieving the best chemical reaction effect. By adjusting the ratio of these two compounds, the progress of the reaction and the performance of the final product can be optimized.
[0040] In certain embodiments, a method for preparing a hydrophilic ceftriaxone magnetic molecularly imprinted polymer comprises the following detailed steps:
[0041] First, step S1 involves preparing a magnetic iron-aluminum mixed hydroxide suspension. Specifically, the magnetic iron-aluminum mixed hydroxide suspension can be formed by dissolving the magnetic iron-aluminum mixed hydroxide in deionized water.
[0042] Next, step S2 includes dissolving ceftriaxone and 3-amino-1,2,4-triazole in deionized water. Ceftriaxone is a broad-spectrum antibiotic, and 3-amino-1,2,4-triazole is a commonly used organic small molecule. After the two substances are dissolved, they are mixed with the previously prepared magnetic iron-aluminum mixed hydroxide suspension and stirred thoroughly to ensure that ceftriaxone and 3-amino-1,2,4-triazole are evenly distributed in the suspension.
[0043] Then, step S3 involves adding ethylene glycol dimethacrylate and ammonium persulfate to the mixed solution obtained in step S2. Ethylene glycol dimethacrylate is a cross-linking agent that can form a stable polymer network structure with ceftriaxone and 3-amino-1,2,4-triazole. Ammonium persulfate is used as an initiator to start the polymerization reaction. After adding these substances, the mixture is continued to be stirred, and then the polymerization reaction is carried out in an inert atmosphere to prevent oxygen from interfering with the reaction. After the polymerization reaction is completed, the supernatant is removed and the precipitate is collected, which is the desired hydrophilic ceftriaxone magnetic molecular imprinting polymer.
[0044] Through the above steps, a hydrophilic ceftriaxone magnetic molecular imprinted polymer with a specific recognition site can be successfully prepared. The polymer not only has good magnetic responsiveness, but also can effectively recognize and adsorb ceftriaxone molecules in an aqueous environment.
[0045] In some embodiments, the ratio of the magnetic iron-aluminum mixed hydroxide, ceftriaxone, 3-amino-1,2,4-triazole, ethylene glycol dimethacrylate and ammonium persulfate is 8-12g: 0.18-0.22mmol: 3.5-4.5mmol: 15-25mmol: 1g. This specific ratio can ensure that the components can react effectively during the preparation process to obtain the desired magnetic composite material. By precisely controlling the ratio of these components, the magnetic properties and adsorption properties of the material can be optimized, so that it can show better effects in practical applications.
[0046] In some specific embodiments, during the polymerization reaction, the reaction temperature is set in the range of 38 to 42 ° C. Such a temperature range helps to ensure that the reaction is carried out under suitable conditions, and neither the occurrence of side reactions due to excessively high temperatures nor the reaction rate and the efficiency of product generation due to excessively low temperatures are affected. At the same time, the stirring speed of the reaction system is controlled at 280-330 revolutions per minute, and such a speed can ensure that the reactants are fully mixed in the reaction system, thereby improving the uniformity of the reaction and the consistency of the product. In addition, the reaction time is set between 4.5 and 5.5h, and this time range can ensure that the reaction is sufficiently carried out, so that the reactants can be converted into the target product as completely as possible, while avoiding unnecessary energy consumption and the occurrence of side reactions caused by excessively long reaction times. In summary, by accurately controlling the reaction temperature, speed and time, the polymerization reaction can be effectively carried out to obtain high-quality polymer products.
[0047] In some embodiments, the hydrophilic ceftriaxone magnetic molecular imprinted polymer is dried and then washed with a methanol-acetic acid-water mixture and a sodium dihydrogen phosphate solution in sequence until no template molecules are detected in the washing solution, and then dried for later use.
[0048] The embodiment of the present invention provides a hydrophilic ceftriaxone magnetic molecular imprinted polymer prepared by a specific method. The polymer has unique hydrophilic properties and can effectively recognize and bind to ceftriaxone molecules, thereby playing an important role in the detection and separation process of ceftriaxone.
[0049] Specifically, the embodiments of the present invention relate to a hydrophilic ceftriaxone magnetic molecular imprinted polymer, which is obtained by an innovative preparation method. This method not only ensures the hydrophilicity of the polymer, but also gives it the specific recognition ability of ceftriaxone molecules. This hydrophilic ceftriaxone magnetic molecular imprinted polymer has a wide range of application prospects in the detection and analysis of ceftriaxone.
[0050] The embodiment of the present invention also provides a method for applying the hydrophilic ceftriaxone magnetic molecular imprinted polymer to ceftriaxone detection. By utilizing the specific binding ability of this polymer, high sensitivity and high selectivity detection of ceftriaxone can be achieved. This method not only improves the accuracy of detection, but also simplifies the operation steps, and has high practical value.
[0051] Chemicals and reagents of the embodiments and comparative examples of the present invention
[0052] Ethylene glycol dimethyl acrylate (EGDMA, GR grade, Guangdong Wengjiang Chemical Reagent Co., Ltd.); 3-amino-1,2,4-triazole (ATA, purity 96%, Shanghai Aladdin Reagent Co., Ltd.); ammonium persulfate (APS, purity 99.99%, Shanghai Aladdin Reagent Co., Ltd.); ammonium ferrous (II) sulfate hexahydrate (purity 99.99%, Shanghai Aladdin Reagent Co., Ltd.); aluminum chloride hexahydrate (purity 99.99%, Shanghai Aladdin Reagent Co., Ltd.); sodium hydroxide (AR grade, Xilong Scientific Co., Ltd.); sodium dihydrogen phosphate (AR grade, Xilong Scientific Co., Ltd.); acetonitrile (chromatographic grade, Merck, Germany), methanol (chromatographic grade, Fisher Scientific, UK), formic acid (AR grade, Merck, Germany) and glacial acetic acid (AR grade, Shanghai Aladdin Reagent Co., Ltd.).
[0053] Ceftriaxone sodium standard (purity 97%, Shanghai Yuanye Biotechnology Co., Ltd.): Prepared into 1 mg / mL stock solution, stored in a -20°C refrigerator away from light. Take out and thaw before use, and dilute in proportion to obtain a standard working solution.
[0054] Instruments and equipment of the embodiments of the present invention and comparative examples
[0055] TSQAltisPlus high performance liquid chromatography-tandem mass spectrometer equipped with electrospray ion source (ThermoFisherScientific (FEI) Company, USA), IRAffinity-1 Fourier transform infrared spectrometer scanner (Shimadzu Corporation, Japan), NovaNanoSEM scanning electron microscope (ThermoFisherScientific (FEI) Company, USA), TalosF200s transmission electron microscope (ThermoFisherScientific (FEI) Company, USA), 7410 vibrating sample magnetometer (LakeShore Company, USA), LC-ES-60SH mechanical stirrer (Shanghai Lichen Bangxi Instrument Technology Co., Ltd.), MS3 vortex mixer (IKA Company, Germany), LC-WB-2 constant temperature water bath (Shanghai Lichen Bangxi Instrument Technology Co., Ltd.), MT008-C vacuum glove box (Changsha Miqi Instrument Equipment Co., Ltd.) and DHG-9245A electric heating blast drying oven (Shanghai Yiheng Scientific Instrument Co., Ltd.), Milli-Q water purification system.
[0056] Example 1
[0057] Preparation of MMH
[0058] MMH was prepared by coprecipitation. Take 7.84 g (20 mmol) of (NH4) 2 Fe(SO 4 ) 2 6H 2 O and 2.41 g (10 mmol) of AlCl 3 6H 2 O was added to 400 mL of deionized water and mechanically stirred until completely dissolved. 50 mL of 3 mol / L NaOH was quickly added and mechanically stirred at 500 r / min for 10 min. After the reaction was completed, the stratification was allowed to stand, the supernatant was discarded, the black product was collected by a magnet, and washed 3 times with 400 mL of deionized water. The prepared iron-aluminum MMH was transferred to a 50 mL wide-mouth bottle, and an appropriate amount of deionized water with a pH of 7 was added to the upper layer. It was stored at room temperature for later use.
[0059] Preparation of CEF-MMIP
[0060] Weigh 10±0.02g of the prepared iron-aluminum MMH in a 250mL wide-mouthed conical flask, add 100mL of deionized water, and stir mechanically at 500r / min until completely dispersed, continue for 10min, and prepare an iron-aluminum MMH suspension. Take another 250mL conical flask, weigh 32.3mg (0.2mmol) of CEF1 and 36.3mg (4mmol) of ATA3, dissolve them in 100mL of deionized water, add them to the MMH suspension after they are completely dissolved, continue mechanical stirring for 30min, add 3.8mL of crosslinker EGDMA (20mmol), continue stirring for 30min, and quickly add 1.00g of APS for polymerization. The mixture is transferred to a vacuum glove box pre-filled with nitrogen, and the polymerization reaction is carried out for 5h at 40℃ water bath and 300r / min. After the reaction is completed, the supernatant is discarded, the product is collected, and then the unreacted template molecules on the surface of the product are washed off with deionized water, and dried at 80℃ to constant weight. The dried product was washed with methanol-acetic acid-water (6:1:3, V / V / V) and 0.15 mol / L sodium dihydrogen phosphate solution (pH=7) in sequence until no template molecules were detected in the washing solution, and then dried at 80°C for later use.
[0061] Comparative Example 1
[0062] Preparation of Magnetic Non-Molecularly Imprinted Polymer (MNIP)
[0063] The preparation process of MNIP is the same as that of CEF-MMIP except that no template molecule is added.
[0064] Test Example 1
[0065] CEF-MMIP and MNIP characterization
[0066] X-ray diffraction (XRD)
[0067] Iron oxide has four crystal structures, γ-Fe 2 O 3 with Fe 3 O 4 The crystal structures are roughly the same, belonging to the inverse spinel structure. The XRD patterns of MMH, MNIP and CEF-MMIP are shown in Figure 1 As shown. The XRD diagram shows that the three samples have diffraction peaks at 30.4°, 35.8°, 43.2°, 53.7°, 57.5° and 63.1°, corresponding to γ-Fe 2 O 3 The diffraction peaks at 21.3° and 36.8° correspond to γ-Al(OH) at six crystal planes (220), (311), (400), (422), (511) and (440), respectively. 3The XRD results are consistent with those of γ-Fe 2 O 3 (39-1346) and γ-Al(OH) 3 (7-0324) is very consistent, indicating that the product is a complete crystallized γ-Fe 2 O 3 and γ-Al(OH) 3 The results show that the molecular imprinting layer was successfully coated on the surface of FeAl-MMH. Since the surface of MNIP and CEF-MMIP was covered with the molecular imprinting layer, the intensity of all diffraction peaks of MNIP and CEF-MMIP was weaker than that of FeAl-MMH, but the physical structure of the magnetic nano-oxide did not change during the polymerization process.
[0068] Fourier Transform Infrared Spectroscopy (FTIR)
[0069] The FTIR spectra of Fe-Al-MMH, MNIP and CEF-MMIP are shown in Figure 2. 800 cm -1 The following absorption peaks are caused by the stretching and bending vibrations of iron and aluminum oxides in FeAl MMH. -1 The broad peak between 1630cm -1 The characteristic absorption peak at 3200-3500cm is the OH bond vibration peak of water. From the FTIR spectra of MNIP and CEF-MMIP, we can see that -1 Nearby (NH stretch), 1610~1660cm -1 (C=N) and 1318cm -1 、1260cm -1 The peaks of (aromatic secondary amine) are all characteristic absorption peaks of ATA, while 950cm -1 、860cm -1 The characteristic absorption peak is caused by the out-of-plane bending vibration of the CH substituted by triazole, which indicates that ATA participates in the polymerization reaction. -1 (C=O stretching) and 1100-1200cm -1 The EGDMA characteristic absorption peak of (COC stretching) confirmed the presence of the crosslinker in the polymer. The peaks of MMIP and MNIP were basically the same, with no significant difference, indicating that the main functional groups of CEF-MMIP and MNIP were the same, and the template molecule ceftriaxone in CEF-MMIP was basically eluted cleanly. The infrared spectrum results proved that the magnetic molecular imprinting polymer CEF-MMIP had been successfully prepared.
[0070] Transmission electron microscopy (TEM) and scanning electron microscopy (SEM)
[0071] In order to further reveal the microscopic characteristics of the three materials, MMH, MNIP and CEF-MMIP, transmission electron microscopy was used to obtain high-resolution images of the polymers. Figure 3 The TEM images of MMH, MNIP and CEF-MMIP are shown in Figure 2. The morphological characteristics of the three were studied by transmission electron microscopy. Figure 3 As shown in (a), particles of different sizes and irregular shapes were observed in the TEM image of MMH. Figure 3 (a), (b) and (c) show an additional light grey outer layer, which indicates that the polymer layer has been successfully prepared on the MMH surface.
[0072] SEM was used to further analyze the morphology and size of MMH, MNIP and CEF-MMIP. Figure 4 As shown in (a), MMH presents a spherical morphology and is tightly aggregated together. After polymerization ( Figure 4 b and 4c), MNIP and CEF-MMIP particles are irregular in shape and uneven in size. Figure 4 c) The surface is relatively rough and has a loose and porous structure, which can play a role in the specific adsorption of CEF. Although the microstructure of the imprinted cavity on the surface of CEF-MMIP cannot be observed by SEM, the surface of CEF-MMIP is rough, which may be caused by the imprinted cavity left after eluting CEF. In addition, the magnetic particle size of MNIP and CEF-MMIP also increased due to the formation of surface polymers.
[0073] Test Example 2
[0074] Magnetic properties analysis
[0075] The superparamagnetism and saturation magnetization of MMH, MNIP and CEF-MMIP were tested by vibrating sample magnetometer at pH 7, temperature 25°C and water as dispersant. The results were expressed as hysteresis loops. The magnetic separation effect after CEF-MMIP adsorption was also photographed. The scanning speed of the vibrating sample magnetometer was 1 degree per minute with a step size of 0.02 degrees.
[0076] Figure 5The hysteresis curves (VSM) of the prepared MMH, MNIP and CEF-MMIP. It can be observed from the figure that all the test materials show a centrally symmetrical state, which is a common characteristic of ferromagnetic materials. Further analysis shows that saturation magnetization and hysteresis loops appear in the curves. These two important features indicate that the prepared MMH, MNIP and CEF-MMIP have superparamagnetic properties. Superparamagnetism is a special magnetic state that allows these materials to be quickly adsorbed by a magnet under the action of an external magnetic field and quickly lose their magnetism after the external magnetic field is removed. Specifically, the magnetization intensities of MMH, MNIP and CEF-MMIP are 8.4, 3.6 and 2.3emu / g, respectively (the magnetic materials were not sieved with a standard test sieve). This shows that with the increase of the polymer shell structure, the magnetic strength of the material gradually decreases. The reason for this decrease can be attributed to the shielding effect of the polymer shell on the surface of MMH, that is, the presence of the polymer shell weakens the material's ability to respond to the external magnetic field. From Figure 5 As can be seen in the figure, CEF-MMIP can be evenly dispersed in water, which provides convenient conditions for its application in solution systems. Although its magnetization intensity is relatively weak, CEF-MMIP can achieve rapid separation within 30 seconds under the action of an external magnetic field. This result fully proves that the polymer has good magnetic properties and can meet the needs of rapid separation in practical applications.
[0077] Test Example 3
[0078] Static adsorption
[0079] Weigh 5±0.02 mg CEF-MMIP and MNIP respectively into a 50 mL centrifuge tube, add 10 mL 1-5 μg / mL ceftriaxone standard solution, and vortex for 30 seconds. Take the supernatant and filter it through a 0.22 μm filter membrane. Detect it by HPLC-MS / MS, measure it three times in parallel, and calculate the adsorption amount Q. The adsorption amount calculation formula (1) is as follows:
[0080] Q=V(C 0 -C e ) / m(1)
[0081] Where V (mL) is the volume of the solution, m (mg) is the mass of the adsorbent, and C 0 and C e (μg / mL) are the initial concentration and equilibrium concentration of the solution, respectively.
[0082] The Scatchard calculation formula (2) is as follows:
[0083] Q / C e =-Q / K D +Q max / K D (2)
[0084] Where Q (mg / g) is the adsorption capacity at equilibrium, C e (μg / mL) is the equilibrium concentration, K D is the dissociation constant, Q max (mg / g) is the apparent maximum adsorption capacity.
[0085] The calculation formulas of Langmuir (Formula 3) and Freundlich (Formula 4) isothermal adsorption models are as follows:
[0086] C e / Q e =C e / Q max +1 / (K L Q max )(3)
[0087] QUR e =1 / nlnC e +lnK F (4)
[0088] Among them, 1 / n represents the empirical coefficient of Freundlich, K L (L / mg) represents the Langmuir constant, K F (L / g) represents Freundlich's constant, Q (mg / g) is the binding amount of ceftriaxone, Q max (mg / g) Maximum binding capacity at equilibrium, C e (μg / mL) represents the equilibrium concentration of MMIP and MNIP.
[0089] In order to further explore the binding performance of CEF-MMIP and MNIP, a static adsorption experiment was conducted. Under constant temperature conditions, the adsorption amounts of CEF-MMIP and MNIP in ceftriaxone standard solutions of different mass concentrations were measured. The experimental results are shown in Figure 2. Figure 6As shown in the figure, with the increase of CEF concentration in the solution, the adsorption capacity of CEF-MMIP and MNIP both showed a steady growth trend. It can be observed from the figure that the adsorption capacity of CEF-MMIP is always higher than that of MNIP, which is mainly due to its unique imprinting sites, which can specifically recognize and tightly bind to the target molecules. When the CEF concentration reaches 4μg / mL, the adsorption of CEF-MMIP reaches saturation. As the CEF concentration gradually increases, the number of target molecules that can be adsorbed by the imprinting sites of CEF-MMIP also increases. Especially in the concentration range of 1-3μg / mL, its adsorption capacity rises rapidly, showing efficient adsorption characteristics. However, with the further increase of the initial concentration, the steric hindrance effect between the target molecules and the magnetic material gradually emerges, causing the increase rate of the adsorption amount to slow down until a stable adsorption equilibrium state is reached. In contrast, MNIP can only perform non-specific adsorption due to the lack of specific imprinting sites, so its adsorption effect is much lower than that of CEF-MMIP. This comparison further highlights the advantages of CEF-MMIP in specific adsorption.
[0090] In order to further evaluate the binding characteristics and number of binding sites of CEF-MMIP, the Scatchard model was used for detailed analysis. Figure 7 From the data, we can clearly see that there are two obvious straight lines in the Scatchard analysis of CEF-MMIP, and these two straight lines are composed of two linear parts with different slopes. This phenomenon shows that the binding sites of CEF-MMIP are heterogeneous, that is, they correspond to high-affinity specific binding sites and low-affinity nonspecific binding sites. In order to further quantify the characteristics of these binding sites, K D value (dissociation constant) and Q max For CEF-MMIP, the K values of its high-affinity and low-affinity binding sites are D The values were 0.052 and 0.082 mg / L, respectively, and the corresponding Q max The values of MNIP and CEF-MMIP were 4.48 and 6.74 mg / g, respectively. At the same time, the same Scatchard analysis was performed on MNIP. Unlike the complex graph of CEF-MMIP, the Scatchard graph of MNIP only shows a straight line, which indicates that its binding sites are relatively uniform and lack specificity. By calculation, the K value of MNIP was obtained. D and Q max The values were 0.14 mg / L and 3.16 mg / g, respectively. By comparing the Scatchard analysis results of CEF-MMIP and MNIP, it was found that CEF-MMIP had a lower K D value and higher Qmax This fully demonstrates that CEF-MMIP has a stronger specific adsorption capacity for ceftriaxone than MNIP. This result has important guiding significance for the further development and application of CEF-MMIP in the separation, purification and detection of antibiotics such as ceftriaxone.
[0091] On the basis of previous studies, in order to further explore the mechanism of static adsorption, the Langmuir and Freundlich isotherm adsorption models were used for detailed analysis. Figure 8 , 9 Both models are classic adsorption models that provide a deeper understanding of the interaction between the adsorbent and the target molecule. Figure 8 It can be seen that the points in the figure are closely around the fitting line, showing a good fitting effect. At the same time, the relevant adsorption parameters are also calculated, and these data are summarized in Table 1 for subsequent analysis and comparison. From the point of view of fit, the adsorption behavior of CEF-MMIP is more consistent with the Langmuir adsorption isotherm model, and its R 2 The value reached 0.9991, which is close to 1, indicating that the experimental data is in good agreement with the model prediction. This finding means that the adsorption of ceftriaxone by the prepared CEF-MMIP is mainly monolayer adsorption, that is, the ceftriaxone molecules form a uniform adsorption layer on the surface of CEF-MMIP, without forming a multilayer stack. In the Langmuir model, K L The value is an important parameter, which represents the strength of adsorption capacity. Specifically, K L The larger the value, the stronger the adsorption capacity of the adsorbent for the target molecule. L The K value of CEF-MMIP was found L The value was 12.72, which was much higher than that of MNIP (5.94). This significant difference further confirmed that CEF-MMIP had a stronger adsorption capacity for ceftriaxone, which was mainly attributed to its unique imprinting site and highly specific recognition mechanism.
[0092] Table 1 Adsorption isotherm fitting parameters of CEF-MMIP and MNIP
[0093]
[0094] Test Example 4
[0095] Dynamic adsorption
[0096] Weigh 5±0.02 mg CEF-MMIP and MNIP respectively into 50 mL centrifuge tubes, add 10 mL of 5 μg / mL ceftriaxone standard solution, vortex for 10, 20, 30, 40, 50, 60 and 70 seconds respectively, and separate by external magnetic field. Take the supernatant and filter it through 0.22 μm filter membrane, HPLC-MS / MS detection, and measure it three times in parallel to calculate its adsorption amount Q.
[0097] To further evaluate the adsorption mechanism, the adsorption kinetics of ceftriaxone on CEF-MMIP and MNIP were studied. The experimental data were fitted with the two most common kinetic models, namely the pseudo-first-order equation and the pseudo-second-order equation. The mathematical expressions of these two models are shown in equations (5) and (6).
[0098] ln(Q e -Q t )=lnQ e -k 1 t(5)
[0099] t / Q t =1 / k 2 Q e 2 +t / Q e (6)
[0100] Among them, Q e and Q t are the amount of ceftriaxone adsorbed on CEF-MMIP and MNIP at equilibrium and time t (min), respectively (mg / g), k 1 is the first-order rate constant and k 2 is the second-order rate constant (g / mg / min).
[0101] like Fig.10As shown, it can be clearly seen that the kinetic adsorption curves of CEF-MMIP and MNIP change with the extension of adsorption time. Both curves show a trend of gradually increasing first and then stabilizing, which reflects the adsorption process from rapid adsorption in the early stage to adsorption equilibrium in the later stage. It is worth noting that both adsorbents can reach adsorption equilibrium within 30s, indicating that their adsorption rates are very fast. However, under the same conditions, CEF-MMIP exhibits a higher adsorption capacity than MNIP, thanks to the unique imprinted cavity structure of CEF-MMIP, which enables it to capture and bind ceftriaxone molecules more efficiently. In the early stage of adsorption, ceftriaxone molecules are rapidly adsorbed by a large number of available imprinted cavities on the surface of CEF-MMIP, so the adsorption rate is very fast at this stage. As the adsorption process proceeds, by the middle stage of adsorption, most of the imprinted cavities have been occupied, which leads to a certain resistance to the diffusion of ceftriaxone molecules in CEF-MMIP, so the adsorption rate begins to slow down gradually. When the adsorption reaches equilibrium, most of the imprinted cavities on the surface of CEF-MMIP have been occupied by ceftriaxone molecules. At this time, repulsion occurs between the ceftriaxone molecules adsorbed on CEF-MMIP and the remaining ceftriaxone molecules in the solution, which makes it difficult for the ceftriaxone molecules in the solution to be adsorbed on CEF-MMIP. Therefore, the adsorption amount remains basically unchanged at this stage and reaches a stable equilibrium state. This process fully demonstrates that CEF-MMIP, as an efficient and specific adsorbent, has significant advantages and application potential in the adsorption and separation process of ceftriaxone.
[0102] The kinetic fitting results of the adsorption behavior of CEF-MMIP and MNIP on CEF are shown in Fig.11 , 12 As shown. Through comparative analysis, it was found that the correlation coefficients of the pseudo-second-order adsorption kinetic model fitting of CEF-MMIP and MNIP were significantly higher than the correlation coefficient of the pseudo-first-order adsorption kinetic model. This shows that the pseudo-second-order model can more accurately describe the adsorption behavior of ceftriaxone by these two adsorbents. Then, the equilibrium adsorption amount Q of the pseudo-second-order adsorption kinetics was calculated based on the model. e , for CEF-MMIP and MNIP, the values are 6.19 and 2.94 mg / g, respectively (see Table 2 for detailed data). These calculated values are very close to the actual adsorption amounts observed in the experiment, further verifying the accuracy of the quasi-secondary adsorption kinetic model. It shows that the adsorption of ceftriaxone by CEF-MMIP is mainly based on a chemical adsorption mechanism rather than a simple physical adsorption. This chemical adsorption involves chemical bonding between the adsorbent and the target molecule, so it has a stronger binding force and higher selectivity. At the same time, this also means that the adsorption process does not involve mass transfer processes in the solution, thereby further improving the adsorption efficiency and stability.
[0103] Although the saturated adsorption capacity of CEF-MMIP prepared by the embodiment of the present invention on CEF is relatively low, it can still meet the detection requirements of actual samples. Compared with the previous preparation method, the material prepared by the embodiment of the present invention only takes 30 seconds to balance, which is much better than the existing research and meets the needs of rapid detection. In addition, the embodiment of the present invention uses water as a porogen, which reduces the use of organic solvents, reduces costs and reduces pollution to the environment.
[0104] Table 2 Adsorption kinetics fitting parameters
[0105]
[0106] In summary, the embodiment of the present invention uses MMH as a carrier, CEF as a template molecule, ATA as a functional monomer, EGDMA as a cross-linking agent, APS as an initiator, and water as a porogen to prepare a hydrophilic magnetic molecular imprinted polymer for the selective enrichment of ceftriaxone. Characterization and adsorption experiments have shown that the hydrophilic CEF-MMIP synthesized in the study has a specific recognition site, a fast adsorption rate, and reaches adsorption equilibrium within 30s. The equilibrium adsorption capacity of CEF-MMIP is 6.30mg / g, and the adsorption of CEF conforms to the quasi-secondary kinetic adsorption model, and the adsorption behavior is mainly chemical adsorption. Magnetic performance analysis proves that CEF-MMIP can be quickly separated under a magnetic field without cumbersome centrifugation or filtration. Therefore, the magnetic molecular imprinted polymer can be used as a magnetic adsorbent for the rapid selective enrichment and separation of CEF in food detection. And the preparation method has the advantages of low cost, hydrophilicity, green synthesis, etc., and has broad application prospects.
[0107] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A method for preparing a hydrophilic ceftriaxone magnetic molecular imprinted polymer, characterized in that: The preparation method comprises the following steps: using magnetic iron-aluminum mixed hydroxide as a carrier, ceftriaxone as a template molecule, 3-amino-1,2,4-triazole as a functional monomer, ethylene glycol dimethacrylate as a crosslinking agent, ammonium persulfate as an initiator, and water as a porogen to prepare a hydrophilic ceftriaxone magnetic molecular imprinting polymer.
2. The preparation method according to claim 1, characterized in that: The preparation method of the magnetic iron-aluminum mixed hydroxide is a co-precipitation method.
3. The preparation method according to claim 2, characterized in that: Take (NH4)2Fe(SO4)2·6H2O and AlCl3·6H2O and add them to deionized water, stir until completely dissolved, add NaOH, stir to react, let stand to separate layers, discard the supernatant, and collect the black product, which is the magnetic iron-aluminum mixed hydroxide.
4. The preparation method according to claim 3, characterized in that: The molar ratio of (NH4)2Fe(SO4)2·6H2O to AlCl3·6H2O is 1.8-2.2:
1.
5. The preparation method according to claim 1, characterized in that: The specific steps include: S1, preparing a magnetic iron-aluminum mixed hydroxide suspension; S2, dissolving ceftriaxone and 3-amino-1,2,4-triazole in deionized water, and then mixing and stirring with the magnetic iron-aluminum mixed hydroxide suspension; S3, adding ethylene glycol dimethacrylate and ammonium persulfate to the solution obtained in step S2, stirring, subjecting the mixed product to a polymerization reaction in an inert atmosphere, removing the supernatant, and collecting the product, which is the hydrophilic ceftriaxone magnetic molecular imprinting polymer.
6. The preparation method according to claim 5, characterized in that: The ratio of the magnetic iron-aluminum mixed hydroxide, ceftriaxone, 3-amino-1,2,4-triazole, ethylene glycol dimethacrylate and ammonium persulfate is 8-12 g: 0.18-0.22 mmol: 3.5-4.5 mmol: 15-25 mmol: 1 g.
7. The preparation method according to claim 5, characterized in that: The polymerization reaction temperature is 38-42° C., the rotation speed is 280-330 r / min, and the reaction time is 4.5-5.5 h.
8. The preparation method according to claim 5, characterized in that: The hydrophilic ceftriaxone magnetic molecular imprinted polymer is dried and then washed with a methanol-acetic acid-water mixture and a sodium dihydrogen phosphate solution in sequence until no template molecules are detected in the washing solution, and then dried for later use.
9. A hydrophilic ceftriaxone magnetic molecular imprinted polymer prepared by the method according to any one of claims 1 to 8.
10. Use of the hydrophilic ceftriaxone magnetic molecular imprinted polymer according to claim 9 in the detection of ceftriaxone.
Citation Information
Patent Citations
Method for preparing magnetic molecularly-imprinted adsorbent
CN104479072A
Amphiphilic acetochlor magnetic molecularly imprinted polymer and preparation method and application thereof
CN106749903A
Preparation method of high-selectivity ceftriaxone sodium magnetic molecularly imprinted polymer
CN111269366A
Carcisterone derivative molecularly imprinted polymer as well as preparation method and application thereof
CN112321763A
Polyvalent imprinted polymer and process of preparation thereof
US20040192869A1